Changes in Endogenous Carotenoids, Flavonoids, and Phenolics of Drought-Stressed Broccoli Seedlings After Ascorbic Acid Preconditioning - Linqi Cai; Lord Abbey; Mason MacDonald (Plants)
Drought is an abiotic disturbance that reduces photosynthesis, plant growth, and crop yield. Ascorbic acid (AsA) was utilized as a seed preconditioning agent to assist broccoli (Brassica oleracea var. italica) in resisting drought. However, the precise mechanism by which AsA improves seedlings’ development remains unknown. One hypothesis is that AsA works via antioxidant mechanisms and reduces oxidative stress. This study aims to confirm the effect of varied concentrations of AsA (control, 0 ppm, 1 ppm, or 10 ppm) on seedling growth and changes in the antioxidant status of broccoli seedlings under regular watering or drought stress. AsA increased shoot dry mass, leaf area, net photosynthesis, and water use efficiency in watered and drought-stressed seedlings. AsA significantly (p < 0.001) increased carotenoid content in watered and drought-stressed seedlings by approximately 27% and 111%, respectively. Drought increased chlorophyll b, flavonoids, phenolics, ascorbate, and hydrogen peroxide production in control seedlings, but either had no effect or less effect on plants preconditioned with 10 ppm AsA. There was no improvement in reactive oxygen species scavenging in AsA-preconditioned seedlings compared to the control. The absence or reduction in biochemical indicators of stress suggests that preconditioned broccoli seedlings do not perceive stress the same as control seedlings. In conclusion, the consistent increase in carotenoid concentration suggests that carotenoids play some role in the preconditioning response, though the exact mechanism remains unknown.